2020
DOI: 10.1186/s13756-020-00767-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms affecting the implementation of a national antimicrobial stewardship programme; multi-professional perspectives explained using normalisation process theory

Abstract: Background: Antimicrobial stewardship (AMS) describes activities concerned with safeguarding antibiotics for the future, reducing drivers for the major global public health threat of antimicrobial resistance (AMR), whereby antibiotics are less effective in preventing and treating infections. Appropriate antibiotic prescribing is central to AMS. Whilst previous studies have explored the effectiveness of specific AMS interventions, largely from uniprofessional perspectives, our literature search could not find a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Of the included papers, 61 focussed on clinical audits, 17 on accreditation/certification and 7 on peer reviews. In terms of the evidence levels established by EPOC review group [30], one randomised trial was found [35], two controlled studies [36,37], 66 case studies , and 16 descriptive studies [104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Using the QI-MQCS, the completeness of reporting scores ranged from 4 to 16 (16 being the highest possible score) (S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included papers, 61 focussed on clinical audits, 17 on accreditation/certification and 7 on peer reviews. In terms of the evidence levels established by EPOC review group [30], one randomised trial was found [35], two controlled studies [36,37], 66 case studies , and 16 descriptive studies [104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Using the QI-MQCS, the completeness of reporting scores ranged from 4 to 16 (16 being the highest possible score) (S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have described local audits that were started by intrinsically motivated healthcare professionals on issues they felt to impact on patient care [ 48 , 53 , 61 , 63 , 69 , 82 , 88 , 97 , 99 , 103 ]. In contrast, if healthcare professionals perceive an audit as a ‘side-line’ or ‘mandatory exercise’, rather than a process to contribute to improved quality of care, they will not feel engaged and not put significant effort into the change [ 77 , 118 ]. This is especially true when audits are externally initiated and have a strong organisational focus, sometimes without links to clinical care [ 102 , 104 , 106 108 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though theoretical advances from academia or policy describe nurses’ roles, these are yet to be translated to clinical settings. 28 , 29 Published evidence also suggest that the extent to which these professionals are involved remains a barrier; 30 , 31 however, we recognize not all pharmacists and nurses may be suitably trained for AMS activities, and, where possible, should involve those with specialist knowledge/skills. Patient education on rational antibiotic use was an area that the learners acknowledged pharmacist and nurses to have an important role.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in earlier studies[ 10 , 43 47 ], organisational factors such as a lack of financial and human resources remain important barriers to the implementation of AMS. This could explain why only one-third of hospitals had conducted a follow-up PPS at the time of the survey, as incorporating the PPS throughout the hospital’s AMS activities requires a dedicated and sustainable investment of time and resources.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of social and contextual factors determining antimicrobial prescribing behaviour is increasingly being acknowledged. In recent years, qualitative studies have explored some of the drivers behind hospital prescribing practices, such as medical hierarchies and social norms[ 31 , 47 , 50 , 51 ], the dynamic between immediate, individual patient care and long-term impact on AMR[ 31 , 52 ] and clinical uncertainty[ 51 , 53 ]. Since many of these barriers and driving factors are context-dependent, identifying barriers and strategies to overcome them on a local level should allow hospitals to tailor AMS interventions more precisely and thereby maximise the sustainability of these interventions [ 54 ].…”
Section: Discussionmentioning
confidence: 99%